2007
DOI: 10.1371/journal.pbio.0050061
|View full text |Cite
|
Sign up to set email alerts
|

A Burst-Based “Hebbian” Learning Rule at Retinogeniculate Synapses Links Retinal Waves to Activity-Dependent Refinement

Abstract: Patterned spontaneous activity in the developing retina is necessary to drive synaptic refinement in the lateral geniculate nucleus (LGN). Using perforated patch recordings from neurons in LGN slices during the period of eye segregation, we examine how such burst-based activity can instruct this refinement. Retinogeniculate synapses have a novel learning rule that depends on the latencies between pre- and postsynaptic bursts on the order of one second: coincident bursts produce long-lasting synaptic enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
230
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(240 citation statements)
references
References 47 publications
10
230
0
Order By: Relevance
“…Our previous study using the same coculture preparations showed that synchronized firing activity between thalamic and cortical cells develops during the second week in vitro, when axonal branches are added in great numbers (18). Thus, precise synchrony rather than the overall amounts of pre-and postsynaptic activity for a given period may play an important role in the promotion of axon branching (18,(31)(32)(33)(34), although our investigations did not distinguish between these two possibilities. The NMDA receptor, a coincidence detector of pre-and postsynaptic activity, is likely to be involved in this process (13,35,36).…”
Section: Discussionmentioning
confidence: 59%
“…Our previous study using the same coculture preparations showed that synchronized firing activity between thalamic and cortical cells develops during the second week in vitro, when axonal branches are added in great numbers (18). Thus, precise synchrony rather than the overall amounts of pre-and postsynaptic activity for a given period may play an important role in the promotion of axon branching (18,(31)(32)(33)(34), although our investigations did not distinguish between these two possibilities. The NMDA receptor, a coincidence detector of pre-and postsynaptic activity, is likely to be involved in this process (13,35,36).…”
Section: Discussionmentioning
confidence: 59%
“…After the pairing, the cell is returned to voltage clamp, and the amplitude of the AMPA current is monitored for any change. A similar protocol was recently demonstrated to induce plasticity at the developing retinogeniculate synapse (Butts et al, 2007).…”
Section: Prevalence Of Silent Synapses Over Developmentmentioning
confidence: 86%
“…These results were seen during a period of significant refinement and maturation of retinogeniculate synapses, including increases in AMPA/ NMDA ratios and decreases in the presence of silent synapses (Chen and Regehr, 2000). By varying the timings of presynaptic and postsynaptic burst onsets, Butts et al (2007) also demonstrated that LTP did not depend on burst order, and that longterm depression (LTD) could be induced by separating burst onsets by hundreds to thousands of milliseconds. This supports a model in which the refinement of retinofugal projections not Using a Mann-Whitney U test, we find that the control P3-P4 distribution is different from the control P6 -P7 distribution ( p Ͻ 0.05), whereas the ␤2 Ϫ/Ϫ distributions at P3-P4 and P6 -P7 are not significantly different ( p ϭ 0.6).…”
Section: Model Of Retinal-wave-dependent Synaptic Plasticitymentioning
confidence: 89%
See 1 more Smart Citation
“…This question was first addressed by using information-theoretic approaches (Butts and Rokhsar, 2001) suggesting that information content was mostly preserved when using broad time scales (on the order of seconds, rather than milliseconds). This led to the proposal that information was transmitted at the level of bursts of action potentials, rather than individual action potentials (Butts and Rokhsar, 2001;Butts et al, 2007). To use this information, burst time-dependent plasticity (BTDP) has been proposed, based upon recordings in developing retinogeniculate pathway, mirroring that of spike time-dependent plasticity (STDP) (Butts et al, 2007).…”
Section: Spike-based or Burst-based Rules?mentioning
confidence: 99%